Sociology Departments and Program Review: Chair Perspectives on Process and Outcomes. (January 2021) - Senter, Mary Scheuer; Ciabattari, Teresa; Amaya, Nicole V.
Sociology faculty are accountable to multiple stakeholders to demonstrate that our academic programs are effective and that students are learning. Despite the ubiquity of mandated program review practices, which often include the assessment of student learning, research is lacking on the extent to which these efforts lead to improvements in departmental outcomes and student experiences. Similarly, little research exists on how department leaders experience and evaluate the utility of these efforts. This article uses data from a national survey of sociology departments to document how program review and assessment are enacted in sociology departments and to explore chairs' perspectives on program review processes and its outcomes. The article concludes with a series of recommendations for improving these processes so that faculty time is used well and the experiences of sociology students are enhanced.